Sesquioxide composite laser ceramic and preparation method thereof
Through dry press molding and cold isostatic press molding, combined with adjusting the amount of sintering aid, the contradiction between the thermal conductivity and emission spectrum broadening of existing sesquioxide ceramics is solved, and efficient and low-cost sesquioxide composite laser ceramics are achieved.
Patent Information
- Application Number
- CN202411820716.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-15
AI Technical Summary
While ensuring high thermal conductivity, existing sesquioxide ceramics are difficult to broaden the emission spectrum of ytterbium ions, and multi-layer sintering technology increases production cycle and energy consumption.
The composite ceramic blank is prepared by dry press molding combined with cold isostatic press molding, reducing the solid solution of the two ceramic contact layers, and by changing the amount of sintering additive zirconium dioxide, the optimal sintering temperature of the ceramic is adjusted so that it only requires one vacuum sintering.
It is achieved by increasing the emission spectrum of ytterbium ions and improving the thermal conductivity of ceramics while ensuring high optical transmittance, reducing production costs and time.
Smart Images

Figure CN119822828A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sesquioxide composite laser ceramic and a preparation method thereof, and more specifically to an ytterbium-doped lutetium oxide and ytterbium-doped scandium oxide composite laser ceramic and a preparation method thereof. Background Art
[0002] Rare earth ion doped sesquioxides (such as Lu2O3, Sc2O3 and Y2O3) have the advantages of wide transmission band, wide emission band and high thermal conductivity, and are widely used in high energy physics, biomedicine and military industry. 3 + ) because of its simple energy level structure (only ground state 2 F 7 / 2 and excited state 2 F 5 / 2 Two energy levels), wide absorption band and long fluorescence lifetime, etc. As an active ion, it can be used to generate 1 micron ultrashort ultrafast laser, and is an ideal high repetition rate, high power laser gain medium material. However, due to its high melting point (>2400℃), sesquioxide is difficult to grow into single crystals, while ceramic low temperature preparation technology can prepare large-sized, high-concentration uniformly doped sesquioxide ceramics.
[0003] Sesquioxide ceramics are mainly divided into pure sesquioxide ceramics (such as Lu2O3, Sc2O3 and Y2O3, etc.) and solid solution sesquioxide ceramics (such as (Lu,Sc)2O3, (Lu,Y)2O3 and (Sc,Y)2O3, etc.). Pure sesquioxide ceramics have the advantage of high thermal conductivity (>12W / mK), but because they only have one matrix material, the emission spectrum broadening of doped ions is often small, which is not conducive to subsequent laser experiments. Due to the difference in the quality of the matrix material, solid solution sesquioxide ceramics will produce lattice distortion, which will lead to a broadening of the emission spectrum (>20nm), but the thermal conductivity will decrease accordingly. M. Tokurakawa et al. stacked a piece of Yb:Sc2O3 ceramic and a piece of Yb:Y2O3 ceramic together, and achieved the broadening of the emission spectrum of ytterbium ions in laser experiments (see M. Tokurakawa, et al. Diode-pumped ultrashock-pulse generation based on Yb 3+ :Sc2O3 andYb 3+:Y2O3ceramic multi-gain-media oscillator Opt. Express 17(5)(2009)3353-3361.), it can be seen that the laser ceramics with multi-layer pure sesquioxide structure can achieve the broadening of the emission spectrum of ytterbium ions while ensuring high thermal conductivity. However, the laser ceramics need to sinter a piece of Yb:Sc2O3 ceramic and a piece of Yb:Y2O3 ceramic separately. The two sinterings mean a longer production cycle and higher energy consumption, which increases the production cost. Moreover, the cross-sectional gap between the two ceramics after stacking may cause scattering, which ultimately affects the laser performance.
[0004] The best vacuum sintering temperature of Yb:Lu2O3 laser ceramics is about 1500℃ (see ZYLiu, et al. Microstructure and properties characterization of Yb:Lu2O3 transparent ceramics from
[0005] co-precipitated nano-powders, Int. J. Appl. Ceram. Technol., 20 (6) (2023) 3365-3375.), the optimal vacuum sintering temperature of Yb: Sc2O3 laser ceramics is about 1650 ° C (see G. Toci, et al. Fabrication and laser performances of Yb: Sc2O3 transparent ceramics from different combination of vacuum sintering and hot isostatic pressing conditions, J. Eur. Ceram. Soc., 40 (3) (2020) 881-886.), and there is a difference of about 150 ° C between the two. Therefore, we designed a sesquioxide composite laser ceramic and its preparation method. First, in the process of preparing the powder, by changing the amount of zirconium dioxide added as a sintering aid, the optimal vacuum sintering temperatures of Yb: Lu2O3 and Yb: Sc2O3 ceramics are made consistent, so that only one vacuum sintering is required. After dry pressing, the Yb:Lu2O3 and Yb:Sc2O3 ceramic blanks are tightly placed in a vacuum bag for cold isostatic pressing. The composite ceramic blank has no cross-sectional voids and a small amount of solid solution in the middle contact layer. The composite laser ceramic has the advantages of high thermal conductivity and wide emission spectrum while ensuring high optical transmittance, and is expected to become an ideal ultrashort and ultrafast laser gain medium material. Summary of the invention
[0006] The purpose of the present invention is to provide a sesquioxide composite laser ceramic and a preparation method thereof, more specifically, a ytterbium-doped lutetium oxide and ytterbium-doped scandium oxide composite laser ceramic and a preparation method thereof. By preparing a composite ceramic blank by dry pressing combined with cold isostatic pressing, the solid solution of the two ceramic contact layers can be reduced, and the optimal sintering temperature of the two layers of ceramics can be adjusted by changing the amount of zirconium dioxide added as a sintering aid, so that the composite ceramic only needs to be vacuum sintered once, and the emission spectrum of the ytterbium ion can be broadened and the thermal conductivity of the ceramic can be improved while ensuring high optical transmittance.
[0007] The present invention provides a sesquioxide composite laser ceramic, which is characterized by being composed of a ytterbium-doped lutetium oxide (hereinafter referred to as Yb:Lu2O3) ceramic and a ytterbium-doped scandium oxide (hereinafter referred to as Yb:Sc2O3) ceramic stacked and composited, wherein the molecular formula of the ytterbium-doped lutetium oxide is (Yb: x Lu 2-x O3) 1-m (ZrO2) m , the value ranges of x and m are: 0.01≤x≤0.2, 0.01≤m≤0.1, and the molecular formula of the ytterbium-doped scandium oxide is (Yb y Sc 2-y O3) 1-n (ZrO2) n , the value range of y and n is: 0.01≤y≤0.2, 0.01≤n≤0.1.
[0008] The present invention also provides a method for preparing the above-mentioned sesquioxide composite laser ceramic, which mainly comprises the following steps:
[0009] S1: According to (Yb x Lu 2-x O3) 1-m (ZrO2) m (0.01≤x≤0.2, 0.01≤m≤0.1), prepare Yb:Lu2O3 powder, according to (Yb y Sc 2-y O3) 1-n (ZrO2) n The Yb:Sc2O3 powder was prepared with a stoichiometric ratio of (0.01≤y≤0.2, 0.01≤n≤0.1);
[0010] S2: Loading Yb: Lu2O3 powder into a mold with a thickness of 3-5 mm, dry pressing for 1-3 minutes at a pressure of 1-5 MPa, pressing out a Yb: Lu2O3 ceramic blank, and then taking it out; then loading Yb: Sc2O3 powder into a mold with a thickness of 3-5 mm, dry pressing for 1-3 minutes at a pressure of 1-5 MPa, pressing out a Yb: Sc2O3 ceramic blank;
[0011] S3: placing the two ceramic blanks tightly together in a vacuum bag, and cold isostatically pressing them at a pressure of 200-210 MPa for 2-5 minutes to obtain a composite ceramic blank;
[0012] S4: placing the composite ceramic green body into a vacuum sintering furnace and keeping the temperature at 1500-1700° C. for 5-24 hours to obtain a ceramic sample;
[0013] S5: placing the ceramic sample into a hot isostatic pressing furnace, heating it in an argon atmosphere and a pressure of 200-250 MPa, and keeping it at 1450-1750° C. for 1-5 hours to obtain a composite ceramic;
[0014] S6: placing the composite ceramic into an atmosphere annealing furnace, maintaining the temperature in an oxygen atmosphere at 1000-1300° C. for 5-24 hours, and performing double-sided mirror polishing on the obtained sample to obtain an ytterbium-doped sesquioxide composite laser ceramic.
[0015] Furthermore, in step S2, the material of the mold is graphite or cemented carbide to ensure that the mold does not deform under high temperature and high pressure and is easy to demold.
[0016] Furthermore, in step S3, the vacuum degree in the vacuum bag is less than 10^-3Pa, so as to eliminate pores and bubbles inside the green body and improve the density of the composite ceramic.
[0017] Furthermore, in step S3, the two ceramic blanks are tightly fitted, specifically, the Yb:Lu2O3 ceramic blank is placed on or below the Yb:Sc2O3 ceramic blank.
[0018] Furthermore, in step S4, the vacuum degree of the vacuum sintering furnace is maintained within the range of 10^-6Pa to ensure that there is no influence of oxygen or other impurities during the sintering process, thereby improving the purity of the ceramic.
[0019] Furthermore, in step S5, the purity of the argon gas is not less than 99.999% to avoid the influence of impurities on the performance of the ceramic.
[0020] Technical effects of the present invention:
[0021] The composite ceramic blank is obtained by dry pressing combined with cold isostatic pressing, which can reduce the solid solution and cross-sectional voids of the two ceramic contact layers. Reducing the solid solution part helps to improve the thermal conductivity of the ceramic, and reducing the cross-sectional voids helps to reduce ceramic scattering, which is beneficial to subsequent laser experiments.
[0022] By changing the amount of zirconium dioxide added as a sintering aid, the composite ceramic only needs to be vacuum sintered once, effectively saving time and energy and improving production efficiency. On the premise of ensuring high optical transmittance, the emission spectrum of ytterbium ions can be broadened and the thermal conductivity of ceramics can be improved to meet the needs of high-performance lasers. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of the structure of the sesquioxide composite laser ceramic of the present invention.
[0024] Figure 2 1 and 2. The graphs of (a) transmittance curve, (b) emission spectrum of ytterbium ions and (c) thermal conductivity versus temperature of the composite laser ceramic prepared in Example 1 of the present invention are shown.
[0025] Figure 3 1 and 2. The graphs of (a) transmittance curve, (b) emission spectrum of ytterbium ions and (c) thermal conductivity versus temperature of the composite laser ceramic prepared in Example 2 of the present invention are shown.
[0026] Figure 4 1 and 2. (a) transmittance curve, (b) emission spectrum of ytterbium ions and (c) curve of thermal conductivity varying with temperature of the composite laser ceramic prepared in Example 3 of the present invention.
[0027] Figure 5 1 and 2. (a) transmittance curve, (b) emission spectrum of ytterbium ions and (c) curve of thermal conductivity varying with temperature of the composite laser ceramic prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with the embodiments and accompanying drawings. These examples are only used to illustrate the present invention, but should not be used to limit the protection scope of the present invention.
[0029] The structure of the sesquioxide composite laser ceramic of the present invention is as follows Figure 1 As shown, the ceramic is composed of ytterbium-doped lutetium oxide and ytterbium-doped scandium oxide ceramics stacked up and down, and the molecular formula of the ytterbium-doped lutetium oxide is (Yb x Lu 2-x O3) 1-m (ZrO2) m , 0.01≤x≤0.2, 0.01≤m≤0.1, the molecular formula of the ytterbium-doped scandium oxide is (Yb y Sc 2-y O3) 1-n (ZrO2) n , 0.01≤y≤0.2, 0.01≤n≤0.1.
[0030] Example 1
[0031] According to (Yb 0.01 Lu 1.99 O3) 0.99 (ZrO2) 0.01 Prepare Yb:Lu2O3 powder according to (Yb 0.01 Sc 1.99 O3) 0.97 (ZrO2) 0.03 Prepare Yb:Sc2O3 powder. Put Yb:Lu2O3 powder into the mold with a thickness of 3 mm, dry press for 1 minute under a pressure of 1 MPa, press out the Yb:Lu2O3 ceramic blank, then take it out, put Yb:Sc2O3 powder into the mold with a thickness of 3 mm, dry press for 1 minute under a pressure of 1 MPa, press out the Yb:Sc2O3 ceramic blank; put two ceramic blanks tightly together in a vacuum bag, cold isostatically press for 2 minutes under a pressure of 200 MPa to obtain a composite ceramic blank. Put the ceramic blank into a vacuum furnace and keep it at 1500°C for 5 hours, then put the ceramic sample into a hot isostatic pressing furnace, heat it under an argon atmosphere and a pressure of 200 MPa, and keep it at 1450°C for 1 hour to obtain a composite ceramic. Finally, the composite ceramic was placed in an atmosphere annealing furnace and kept at 1000°C for 5 hours in an oxygen atmosphere. The obtained sample was double-sided mirror polished to obtain a 1 mm thick ytterbium-doped sesquioxide composite laser ceramic.
[0032] Lamda 750 UV / visible / near infrared spectrophotometer was used to measure the transmittance of the sample from 250 to 1500 nm. The transmittance at 1500 nm was 81%, as shown in Figure 2 (a) shown.
[0033] The emission spectrum of the sample was measured using the FLS 920 steady-state / transient fluorescence spectrometer from Edinburgh Instruments, UK, with an excitation source of 980 nm semiconductor diode laser. The full width at half maximum at 1038 nm was 22 nm. Figure 2 (b) as shown.
[0034] The thermal conductivity of the sample was measured at 25-500°C using a laser thermal conductivity meter (NETZSCH LFA467) and a differential scanning calorimeter (Perkin Elmer DSC 8000). The thermal conductivity at 25°C was 10.6 W / (m·K), as shown in Figure 2. Figure 2 (c) as shown.
[0035] Example 2
[0036] According to (Yb 0.02 Lu 1.98 O3) 0.96 (ZrO2) 0.04 Prepare Yb:Lu2O3 powder according to (Yb0.05 Sc 1.95 O3) 0.99 (ZrO2) 0.01 Prepare Yb:Sc2O3 powder. Put Yb:Lu2O3 powder into the mold with a thickness of 4 mm, dry press for 2 minutes at a pressure of 2MPa, press out the Yb:Lu2O3 ceramic blank, then take it out, put Yb:Sc2O3 powder into the mold again with a thickness of 4 mm, dry press for 2 minutes at a pressure of 2MPa, press out the Yb:Sc2O3 ceramic blank; put two ceramic blanks tightly together in a vacuum bag, cold isostatically press for 3 minutes at a pressure of 205MPa to obtain a composite ceramic blank. Put the ceramic blank into a vacuum furnace and keep it at 1550℃ for 10 hours, then put the ceramic sample into a hot isostatic pressing furnace, heat it in an argon atmosphere and a pressure of 210MPa, and keep it at 1550℃ for 2 hours to obtain a composite ceramic. Finally, the composite ceramic was placed in an atmosphere annealing furnace and kept at 1100°C for 10 hours in an oxygen atmosphere. The obtained sample was double-sided mirror polished to obtain a 1 mm thick ytterbium-doped sesquioxide composite laser ceramic.
[0037] The transmittance of the sample in Example 2 at 1500nm is 80%. Figure 3 (a) shows that the full width at half maximum at 1038nm is 20nm, as shown in Figure 3 (b) shows that the thermal conductivity at 25°C is 9.4 W / (m·K), Figure 3 (c) as shown.
[0038] Example 3
[0039] According to (Yb 0.2 Lu 1.8 O3) 0.92 (ZrO2) 0.08 Prepare Yb:Lu2O3 powder according to (Yb 0.15 Sc 1.85 O3) 0.9 (ZrO2) 0.1Prepare Yb:Sc2O3 powder. Put Yb:Lu2O3 powder into the mold with a thickness of 5 mm, dry press for 3 minutes at a pressure of 3MPa, press out the Yb:Lu2O3 ceramic blank, then take it out, put Yb:Sc2O3 powder into the mold with a thickness of 5 mm, dry press for 3 minutes at a pressure of 3MPa, press out the Yb:Sc2O3 ceramic blank; put two ceramic blanks tightly together in a vacuum bag, cold isostatically press for 4 minutes at a pressure of 210MPa to obtain a composite ceramic blank. Put the ceramic blank into a vacuum furnace and keep it at 1650℃ for 20 hours, then put the ceramic sample into a hot isostatic pressing furnace, heat it in an argon atmosphere and a pressure of 220MPa, and keep it at 1620℃ for 3 hours to obtain a composite ceramic. Finally, the composite ceramic was placed in an atmosphere annealing furnace and kept at 1200°C for 15 hours in an oxygen atmosphere. The obtained sample was double-sided mirror polished to obtain a 1 mm thick ytterbium-doped sesquioxide composite laser ceramic.
[0040] The transmittance of the sample in Example 3 at 1500nm is 78%. Figure 4 (a) shows that the full width at half maximum at 1038nm is 19nm, as shown in Figure 4 (b) shows that the thermal conductivity at 25°C is 8.2 W / (m·K), Figure 4 (c) as shown.
[0041] Example 4
[0042] According to (Yb 0.1 Lu 1.9 O3) 0.9 (ZrO2) 0.1 Prepare Yb:Lu2O3 powder according to (Yb 0.2 Sc 1.8 O3) 0.92 (ZrO2) 0.08Prepare Yb:Sc2O3 powder. Put Yb:Lu2O3 powder into the mold with a thickness of 3 mm, dry press for 2 minutes at a pressure of 5 MPa, press out the Yb:Lu2O3 ceramic blank, then put Yb:Sc2O3 powder into the mold with a thickness of 5 mm, dry press for 3 minutes at a pressure of 5 MPa, press out the Yb:Sc2O3 ceramic blank; put two ceramic blanks tightly together in a vacuum bag, cold isostatically press for 5 minutes at a pressure of 200 MPa to obtain a composite ceramic blank. Put the ceramic blank into a vacuum furnace and keep it at 1700°C for 24 hours, then put the ceramic sample into a hot isostatic pressing furnace, heat it in an argon atmosphere and a pressure of 250 MPa, and keep it at 1750°C for 5 hours to obtain a composite ceramic. Finally, the composite ceramic was placed in an atmosphere annealing furnace and kept at 1300°C in an oxygen atmosphere for 24 hours. The obtained sample was double-sided mirror polished to obtain a 1 mm thick ytterbium-doped sesquioxide composite laser ceramic.
[0043] The transmittance of the sample in Example 4 at 1500nm is 77%. Figure 5 (a) shows that the full width at half maximum at 1038nm is 18nm, as shown in Figure 5 (b) shows that the thermal conductivity at 25°C is 7.6 W / (m·K), Figure 5 (c) as shown.
[0044] The above are only preferred embodiments of the present invention, and are not intended to limit the invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A sesquioxide composite laser ceramic, characterized in that: The ceramic is composed of ytterbium-doped lutetium oxide (Yb: Lu2O3) ceramic and ytterbium-doped scandium oxide (Yb: Sc2O3) ceramic stacked on top of each other. The molecular formula of the ytterbium-doped lutetium oxide is (Yb: x Lu 2-x O3) 1-m (ZrO2) m , the value ranges of x and m are: 0.01≤x≤0.2, 0.01≤m≤0.1, and the molecular formula of the ytterbium-doped scandium oxide is (Yb y Sc 2-y O3) 1-n (ZrO2) n , the value range of y and n is: 0.01≤y≤0.2, 0.01≤n≤0.
1.
2. The method for preparing a sesquioxide composite laser ceramic according to claim 1, characterized in that: The method mainly includes the following steps: S1 powder preparation: according to (Yb x Lu 2-x O3) 1-m (ZrO2) m (0.01≤x≤0.2, 0.01≤m≤0.1), prepare Yb:Lu2O3 powder, according to (Yb y Sc 2-y O3) 1-n (ZrO2) n The Yb:Sc2O3 powder was prepared with a stoichiometric ratio of (0.01≤y≤0.2, 0.01≤n≤0.1); S2 dry pressing: the Yb: Lu2O3 powder obtained in step S1 is charged into a mold with a thickness of 3-5 mm, and dry pressed for 1-3 minutes at a pressure of 1-5 MPa to press out a Yb: Lu2O3 ceramic blank, and then the Yb: Sc2O3 powder obtained in step S1 is charged into the mold with a thickness of 3-5 mm, and dry pressed for 1-3 minutes at a pressure of 1-5 MPa to press out a Yb: Sc2O3 ceramic blank; S3 cold isostatic pressing treatment: the two ceramic blanks obtained in step S2 are tightly fitted together and placed in a vacuum bag, and cold isostatically pressed for 2-5 minutes at a pressure of 200-210 MPa to obtain a composite ceramic blank; S4 vacuum sintering: placing the composite ceramic green body obtained in step S3 into a vacuum sintering furnace and keeping the temperature at 1500-1700° C. for 5-24 hours to obtain a ceramic sample; S5 hot isostatic pressing treatment: placing the ceramic sample obtained in step S4 into a hot isostatic pressing furnace, heating it in an argon atmosphere and a pressure of 200-250 MPa, and keeping it at 1450-1750° C. for 1-5 hours to obtain a composite ceramic; S6 annealing and polishing treatment: the composite ceramic obtained in step S5 is placed in an atmosphere annealing furnace, kept warm in an oxygen atmosphere at 1000-1300° C. for 5-24 hours, and the obtained sample is double-sided mirror-polished to obtain an ytterbium-doped sesquioxide composite laser ceramic.
3. The method for preparing a sesquioxide composite laser ceramic according to claim 2, characterized in that: The composite ceramic blank described in step S2, wherein the Yb:Lu2O3 ceramic blank is placed on or below the Yb:Sc2O3 ceramic blank.
4. The method for preparing the sesquioxide composite laser ceramic according to claim 2, characterized in that: The material of the mold in step S2 is graphite or cemented carbide.
5. The method for preparing the sesquioxide composite laser ceramic according to claim 2, characterized in that: In step S3, the vacuum degree in the vacuum bag is less than 10^-3Pa.
6. The method for preparing the sesquioxide composite laser ceramic according to claim 2, characterized in that: In step S4, the vacuum degree of the vacuum sintering furnace is maintained within the range of 10^-6Pa.
7. The method for preparing the sesquioxide composite laser ceramic according to claim 2, characterized in that: In step S5, the purity of the argon gas is not less than 99.999%.